Hubungan Aceh-Banten dalam Konteks Perniagaan dan Budaya pada Masa Pengaruh Islam Abad Ke-16-17 (Tinjauan dari Penggunaan Gaya Nisan Aceh pada Nisan Makam Sultan-Sultan Banten) - Astri, Yasmina Wikan; Isana, Widiati (UIN Sunan Gunung Djati Bandung, 2025)
This research aims to describe the factors underlying the use of the Aceh-type tombstone style on the tombs of the Sultans of Banten and to reconstruct the relationship between the Aceh Sultanate and the Banten Sultanate during the 16th-17th centuries from the existence of traces of the tombs of the Sultans of Banten using the Aceh-type tombstone style. The method used in this research is the archaeological method using typological analysis to study the shape and size, as well as the analysis of the decorative variety of the Aceh-type tombstones in the Tomb Complex of the Sultans of Banten. In addition, a comparative method is also used by comparing the Aceh tombstone style with the Aceh tombstone style used on the tombstones of the Sultans of Banten. This research uses a historical approach and is carried out in several stages, namely preparation and observation, data collection, data processing, data analysis, and interpretation. Based on the results of the study through literature studies and field studies, it can be concluded that the use of the Aceh tombstone style on the tombstones of the Sultans of Banten cannot be separated from the aspects of trade, Islamic preaching, and cultural contact. The tombstone, in addition to being a grave marker, is also a symbol that shows the position of the buried figure. Thus, the use of Aceh-type tombstones among the kings and clerics of Banten was probably motivated by the reason that the buried figure was a distinguished person in terms of social status. This was probably also aimed at increasing the prestige as well as an effort to legitimize the power of the Banten Sultanate as an Islamic sultanate considering that Samudera Pasai was the oldest Islamic kingdom that had ever triumphed in the archipelago.